Motivations of young women volunteers during COVID-19: A qualitative inquiry in Bahrain - Debashish Sengupta; Dwa Al-Khalifa (Administrative Sciences, 2022)
Volunteering work has played a major role in dealing with the COVID-19 pandemic crisis. Studying volunteering behavior is interesting because it holds many important lessons for businesses to attract and engage their primary stakeholders (employees and customers) and counter the challenges posed by the pandemic. As women make up a large percentage of volunteers, understanding the relationship between motivation and women intending to take up volunteering work during crises is necessary-particularly in collectivist Islamic societies. The present study examined the motivations of young women in Bahrain to volunteer for RT-PCR testing and vaccination drives sponsored by the government during the pandemic. The study also examined the effect of the volunteering experience on the lives of these women. The study was conducted using a mixed qualitative method that included focus groups and in-depth interviews. The research participants were millennial women who had undertaken volunteering during the pandemic. A few in-depth interviews were conducted with male volunteers to examine whether such motivations were influenced by gender. The findings of the research revealed normative, in addition to personal, motivators behind the act of volunteering, with a greater dominance of normative motivations such as the call of the homeland and philanthropy. The influence of the collectivist culture in shaping the normative motivations behind volunteering among these women was visible, and there was also an influence of religion and religious values.
Keywords: 350; volunteering; women; millennial; pandemic; culture